UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENERAPAN METODE ALTERNATIF KOOPERATIF SKRIP PADA MATA PELAJARAN MATEMATIKA DI KELAS II SDN 025 DUMAI TIMUR - Samsuar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This study aimed to describe the learning outcomes through the use of media map. The subjects were students of class II SD 025 Bintan Kecamatan Dumai Timur. This study was conducted over two cycles. Improved learning outcomes in terms of four categories, namely absorption, the effectiveness of learning, mastery learning completeness students both individually and classical completeness and thoroughness of learning outcomes. The instrument used for data collection is an oral test and a written test in the form of worksheets that is done after the process of learning results showed absorption learning outcomes on average 93.93% categorized as very good, very effective learning effectiveness categorized with an average of 90. Meanwhile, mastery learning outcomes of students declared complete 100%